The epidemiology and molecular characterization of Burkholderia pseudomallei in Malaysian Borneo - Yuwana, Podin (Charles Darwin University, 2014)
Melioidosis is a potentially fatal disease caused by Burkholderia pseudomallei which is endemic in Malaysian Borneo. The general aim of this study is to elucidate the molecular epidemiology of B. pseudomallei in Malaysian Borneo. Consistent with the Wallace line theory of separation, genotyping showed Malaysian Borneo clinical B. pseudomallei isolates were more related to Southeast Asian strains than to Australian strains. Whole genome sequencing demonstrated that B. pseudomallei from Sarawak were very closely related to each other. Biochemical testing using VITEK 2 revealed that 25% of B. pseudomallei from Malaysian Borneo were misidentified as B. cepacia, suggesting that specificity of that identification system is regionally dependent. A major and unexpected finding was that 88% of Sarawak B. pseudomallei were gentamicin susceptible, with these B. pseudomallei being restricted to multilocus sequence type ST881 and its single locus variant ST997. A novel nonsynonymous mutation was identified within amrB, an essential component of the AmrAB-OprA multi-drug efflux pump. Reversion of the mutation to the wild-type sequence confirmed the role of this mutation in conferring aminoglycoside and macrolide sensitivity. No environmental B. pseudomallei were isolated from Sarawak but other Burkholderia species were isolated, prompting the formulation of hypotheses to explain the lack of environmental B. pseudomallei. Although inconclusive, experiments showed antagonistic activities by other environmental Burkholderia spp. recovered from environmental sampling studies towards B. pseudomallei and also that gentamicin susceptible B. pseudomallei were slightly xiv less robust than gentamicin resistant strains in competing with other soil microorganisms. This thesis contributed to the understanding of the population structure of B. pseudomallei in Malaysian Borneo, Southeast Asia and globally. The discovery of gentamicin susceptibility in Sarawak B. pseudomallei has significant implications for laboratory diagnosis and environmental sampling of B. pseudomallei in Malaysian Borneo and potentially in other melioidosis endemic regions. Although the exact distributions, quantification and potential environmental hazards and implications of B. pseudomallei in Malaysian Borneo remain uncertain, these studies have led to important research questions now to be explored. Most immediate is further searching for the proposed existence of an as yet unidentified localized niche of B. pseudomallei in Malaysian Borneo.